2020
DOI: 10.1042/bsr20193385
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism and role of intracellular α-ketoglutarate reduction in hepatic stellate cell activation

Abstract: Background: The activation of hepatic stellate cells (HSCs) plays a central role in liver fibrosis. α-ketoglutarate is a natural metabolite and previous studies have shown that increase in intracellular α-ketoglutarate can inhibit HSC activation. Aim: The aim of the present study is to determine the changes and role of intracellular α-ketoglutarate in HSC activation and clarify its mechanism of action. Methods: A human HSC cell line (LX-2) and the primary mouse HSC were used in the present study. We detected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Decreased IDH2 expression limits alpha-ketoglutarate production during HSCs activation, which in turn promotes HSCs activation via a TGF-β1-independent pathway. Therefore, IDH2 and α-ketoglutarate might be potential novel targets to LF therapy [45] . Nestin, a type VI intermediate filament protein, was first identified in neural stem cells (NSCs) and is closely related to the self-renewal of NSCs.…”
Section: Other Roles With Smad Signaling Pathwaymentioning
confidence: 99%
“…Decreased IDH2 expression limits alpha-ketoglutarate production during HSCs activation, which in turn promotes HSCs activation via a TGF-β1-independent pathway. Therefore, IDH2 and α-ketoglutarate might be potential novel targets to LF therapy [45] . Nestin, a type VI intermediate filament protein, was first identified in neural stem cells (NSCs) and is closely related to the self-renewal of NSCs.…”
Section: Other Roles With Smad Signaling Pathwaymentioning
confidence: 99%
“…He et al found that by interfering with the intestinal flora, AKG can promote the differentiation of intestinal cells and slow down the development of colorectal cancer by inhibiting the WNT pathway [12]. In addition, AKG is considered a potential new target for the prevention and treatment of liver fibrosis [13]. Additionally, Tatara et al found that adding AKG to the diet of piglets before and after weaning can effectively promote the formation of bone tissue [14].…”
Section: Introductionmentioning
confidence: 99%
“…As metabolites serve as direct signatures of biochemical activity [20], metabolomics analysis has been used to systematically elucidate the molecular mechanisms of nutritional supplements [13,21]. Meanwhile, 1 H nuclear magnetic resonance (NMR) has been identified as a robust technique for metabonomic applications due to its prominent advantages [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Various nutritional supplements have been employed to promote skeletal muscle hypertrophy and enhance sports performance [ 1 ]. As the intersection of the organic carbon and nitrogen metabolism and simultaneously a critical intermediate in the TCA cycle, α-Ketoglutarate (AKG) has shown pleiotropic effects for improving muscle performance in clinical and animal experiments [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. For example, AKG can reduce intestinal mucosal damage [ 8 ] and inflammation [ 9 ], attenuate the development of colorectal cancer [ 4 ] and liver fibrosis [ 5 ], promote growth [ 6 ], and reduce morbidity and delay aging [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the intersection of the organic carbon and nitrogen metabolism and simultaneously a critical intermediate in the TCA cycle, α-Ketoglutarate (AKG) has shown pleiotropic effects for improving muscle performance in clinical and animal experiments [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. For example, AKG can reduce intestinal mucosal damage [ 8 ] and inflammation [ 9 ], attenuate the development of colorectal cancer [ 4 ] and liver fibrosis [ 5 ], promote growth [ 6 ], and reduce morbidity and delay aging [ 7 ]. Previous works have demonstrated that AKG supplementation can alleviate muscle loss by parenteral administration in a trauma model of patients undergoing total hip replacement [ 2 ], and promote muscle hypertrophy and protein synthesis through Akt/mTOR signaling pathways [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%